2017
DOI: 10.1080/09205063.2017.1409047
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characteristics of the sulfonated chitosan derivatives electrodeposited onto 316l stainless steel surface

Abstract: In order to ameliorate the properties of corrosion resistance and achieve applications in anti-biofouling of 316L stainless steel (SS), a sulfated derivative of chitosan was deposited onto stainless steel surface by an electrochemical method. In detail, chitosan-catechol (CS-CT) was synthesised in the hydrochloric acid solution by the Mannich reaction and then electrodeposited on the surface of the polished 316L stainless steel. The chitosan-catechol deposited SS sample was further modified with maleic anhydri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…In detail, the electrochemical corrosion in stainless steel material is a chemical reaction starts with transfer of electrons from zero valent Fe atom of steel to an external electron acceptor, leading to the release of the metal ions into the encompassing medium and degradation of the metal . The inhibitive behaviour of organic molecules depends on the electron clouds around the donor atoms, higher the electron clouds at the donor atom, more the efficiency as inhibitor.…”
Section: Resultssupporting
confidence: 63%
“…In detail, the electrochemical corrosion in stainless steel material is a chemical reaction starts with transfer of electrons from zero valent Fe atom of steel to an external electron acceptor, leading to the release of the metal ions into the encompassing medium and degradation of the metal . The inhibitive behaviour of organic molecules depends on the electron clouds around the donor atoms, higher the electron clouds at the donor atom, more the efficiency as inhibitor.…”
Section: Resultssupporting
confidence: 63%
“…In the present study, the dissolution of Fe and Ni from the base alloy was observed from ICP-OES analysis, resulting in corrosion of metal started through the transfer of electrons from Fe and Ni to an external electron receiver, hence the release of metal into the solution and degradation of the metal surface. 34 The behavior of any suitable inhibitor strongly depends on the availability of the electrons from donor atoms. If the electron density of the donor atom is high, then the efficiency of the inhibitor increases.…”
Section: Resultsmentioning
confidence: 99%
“…The data presented in this figure were selected based on the literature that contains a direct proof of the observed phenomena, while speculative references were excluded. Regarding the protein adsorption phenomena, for instance, evidences obtained with EIS, CV, QCM [24,29,39,[42][43][44]46,50,[67][68][69][70] and surface analysis techniques [26,29,30,34,44,46,67] were considered as sufficient. Concerning protein-metal binding phenomena, literature containing ICP-OES and AAS [26,27,51,54] evidences was considered.…”
Section: Discussionmentioning
confidence: 99%
“…Adsorption of proteins in biological fluids is one of the initial steps that affects the biocompatibility of the implants inside a human body [66]. BSA adsorption was observed and corroborated either by in-situ electrochemical and/or ex-situ surface analysis techniques by different authors [24,26,29,30,34,39,[42][43][44]46,50,[67][68][69][70]. Indeed, several reviews dedicated to adsorption phenomena involving various proteins exist in the literature [3,9,15,71].…”
Section: Albumin Adsorptionmentioning
confidence: 91%